Uma análise exploratória da jornada flexível de trabalho sob a perspectiva de tutores na educação a distância - Torres, Elvia Florêncio (2009)
Information Age has been providing accelerated development of technologies in teaching, which is making the increase in distance courses and flexibility in the tutors everyday work. In this context, it was aimed to study the influence of flexible work in the development of activities and personal life of the tutors in Distance Education at Universidade Federal do Rio Grande do Norte. More specifically, they have been sought to compare the types of flexibility detected, identifying the extent of the day's work in mentoring; investigating the relationship between flexible working time and productivity; evaluating the Quality of Working Life (QWL) and for Work and Family Relationship of the tutors. Thus, work is justified by the importance of academic and organizational achievement. To meet the goals, it was obtained a sample of 75 respondents (45.73% of the population). The data collection instrument was comprised of 48 variables mainly based by Walton (1975) and Paschoal, Tamayo and Barham (2002). The statistical techniques used were: analysis of frequency, ratio test, factor analysis and regression. The results collected have shown that the presence and distance tutors experience similar realities, but have different profiles; the day of their work is on average three hours daily; in view of the tutors, flexibility has a relation with the production, QWL work-family balance were evaluated in a satisfactory manner and the statistical techniques used have shown significant influence between the QWL and flexible working day. It is therefore concluded that flexibility at work can influence the development of activities and personal life of the tutors. Thus, the flexible working day may be used in a strategy way of routine in many organizations